How Saudi Arabia Experience Corona: A Monthly Analysis Data - Alshammary, Amal F.; Albarqi, Ahmad; Alghamdi, Suad; Alsiary, Rawiah; Alsofyani, Abeer; Almatrrouk, Shaihana; Alonazi, Fahad N.; Alanazi, Mona; Aldahish, Afaf; Alanazi, Aiysha QB.; et al. (International Journal of Innovative Research in Medical Science, 2024)
This study provides evidence of the situation in Saudi Arabia during the COVID-19 pandemic. The Saudi government has taken significant action in response to the outbreak by putting in place measures to restrict the ability of the virus to spread. Cases, recoveries, and deaths were meticulously documented using MOH and/or WHO official sources. Our findings indicate that the number of confirmed cases and fatalities between May 2020 to November 2021 has decreased significantly, and the rate of recovery has been consistently strong. Furthermore, our study examined the rates of new cases and deaths in Saudi Arabia during the pandemic using Spearman's rank correlation coefficient. Overall, our findings indicate a moderate link between new cases and death rates due to the country’s rigorous control during the pandemic and availability of an advanced health care system. In addition, our study documented the country’s nationwide vaccination campaign conducted with locations set up in many major cities. As of May 2022, a total of 64 million doses of the vaccine had been delivered to citizens and anyone with permanent residency in the country to control the spread of the disease. According to the data that has been given in this study, advanced health care system, widespread immunization efforts, and public awareness campaigns in the Kingdom of Saudi Arabia were effective in limiting the virus's capacity to spread further during COVID-19 pandemic.